2020
DOI: 10.1136/jclinpath-2020-206570
|View full text |Cite
|
Sign up to set email alerts
|

Mutational profiling in suspected triple-negative essential thrombocythaemia using targeted next-generation sequencing in a real-world cohort

Abstract: Essential thrombocythaemia (ET) is driven by somatic mutations involving the JAK2, CALR and MPL genes. Approximately 10% of patients lack driver mutations and are referred as ‘triple-negative’ ET (TN-ET). The diagnosis of TN-ET, however, relies on bone marrow examination that is not always performed in routine practice, and thus in the real-world setting, there are a group of cases with suspected TN-myeloproliferativeneoplasm.In this real-world cohort, patients with suspected TN-ET were initially rescreened fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Molecular profiling of triple-negative ET, using targeted gene panels or whole-exome sequencing, revealed the presence of so-called "non-driver" mutations. These variants may chronologically precede or follow the acquisition of driver mutations, thus conferring a selective advantage to neoplastic cells, and affect genes involved in epigenetic regulation (TET2, DNMT3A, ASXL1, EZH2, and IDH1/2), RNA splicing (SF3B1, SRSF2, and U2AF1) and regulation of cytokine signaling (CBL) (25,33). Although mutations in these genes are not restricted to MPNs, their presence can be of diagnostic value in the triplenegative ET cohort, thus providing evidence of clonality (25,33).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular profiling of triple-negative ET, using targeted gene panels or whole-exome sequencing, revealed the presence of so-called "non-driver" mutations. These variants may chronologically precede or follow the acquisition of driver mutations, thus conferring a selective advantage to neoplastic cells, and affect genes involved in epigenetic regulation (TET2, DNMT3A, ASXL1, EZH2, and IDH1/2), RNA splicing (SF3B1, SRSF2, and U2AF1) and regulation of cytokine signaling (CBL) (25,33). Although mutations in these genes are not restricted to MPNs, their presence can be of diagnostic value in the triplenegative ET cohort, thus providing evidence of clonality (25,33).…”
Section: Introductionmentioning
confidence: 99%
“…The JAK2V617F protein is constitutively active leading to the activation of the transcription JAK/STAT pathway, which ensures the control of hematopoietic cell proliferation and survival, causing ET disease 1,12 . JAK2V617F is found in 50% to 60% of ET patients 13 …”
Section: Introductionmentioning
confidence: 99%
“…It plays a crucial role in cellular proliferation, differentiation, and apoptosis. 14 , 15 Somatic mutations in CALR exon 9 are found between 20% and 30% in ET patients 13 The CALR exon 9 mutations are mostly found in patients who are negative for JAK2 V617F. 16 , 17 , 18 Two mutations of CALR gene seem to be more common than all others: type 1 (c.1092_1143del; L367fs*46) in 55% and type 2 (c.1154_1155insTTGTC; K385fs*47) in 35% of ET.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in the presence of "high risk" features (age>60, history of thrombosis), cytoreductive therapy has been demonstrated to reduce the thrombotic risk in MPN patients, but when the diagnosis of MPN is unsure due to the lack of typical histological features, it is not known whether patients would benefit from cytoreductive treatment. Previous studies have shown that NGS could detect variants in 12 to 73% of cases of TN thrombocytosis [2][3][4][5] Variants acquired in genes frequently mutated in myeloid malignancies or germline variants in genes involved in megakaryocytic proliferation, even in the absence of a familial history of thrombocytosis (mainly JAK2, MPL). 6,7 Efforts at finding a common genetic alteration in TN ET have rather reinforced the idea that this group of patients is heterogenous, with clonal or non-clonal hematopoiesis and identification of additional acquired as well as constitutive JAK2, MPL or SH2B3 variants, but no common recurrent anomaly.…”
mentioning
confidence: 99%